Analysis of the Relationship of Marketing Mix with Hospital Image at the Poly Outpatient Clinic of Siloam Mampang Hospital - Ekawati, Sang Ayu Kompiang; Windiyaningsih, Cicilia; Wulandari , Sonya Dewi (IJBLE Scientific Publications Community Inc., 2025)
Competition in healthcare requires hospitals to not only provide quality medical services but also build a positive image in the eyes of the public. This study aims to analyze the relationship between the marketing mix (7Ps: product, price, place, promotion, people, process, and physical evidence) and the image of Siloam Mampang Hospital in 2025. The research method used a quantitative design with a cross-sectional approach. The study sample consisted of 95 outpatients selected incidentally. Analysis included univariate, bivariate (chi-square), and multivariate (logistic regression) tests. The results showed that all dimensions of the marketing mix had a significant relationship with hospital image (p<0.05). Multivariate analysis identified process variables (OR=24.319; p<0.001) and people (OR=8.636; p=0.002) as dominant factors. These findings are in line with service marketing theory, which emphasizes the importance of efficient service flow and healthcare worker interactions in building a positive image. The study recommends strengthening service digitalization, increasing information transparency, and developing healthcare worker communication competencies. An integrated marketing strategy is believed to be able to improve image, competitiveness, and patient loyalty in the future.